How Do Teachers and Students Perceive Human Rights, Citizenship and Democracy Course? - Arife Figen Ersoy; Nur Leman Balbağ; Ömür Gürdoğan Bayır (Sakarya University Journal of Education)
“Human Rights, Citizenship and Democracy” is a course that began to be delivered as of the 2015-2016 school year and aims to teach elementary fourth graders the basic values related to human rights, citizenship and democracy. The aim of this study was to examine students and teachers' experiences and perceptions of the course “Human Rights, Citizenship and Democracy”. In the study, phenomenological research design was adopted in the scope of the qualitative research method. The participants were selected through the maximum diversity sampling technique. In this respect, the study was conducted with eight teachers and 20 students in three elementary schools where students with low, middle and high socio-economic status study in the Eskisehir province. The data were gathered by using the semi-structured interview technique. Thematic analysis was employed in the analysis of the data. As a result, it was found that the students perceived the course as functional since they mostly learned basic democratic values, they also perceived it as the Turkish course because an instructional model based on stories was mostly adopted, and traditional assessment techniques were insufficient in measuring students' gains regarding democratic values. In order to enhance the effectiveness of this course, it seems necessary to update the contents of the course curriculum as well as the coursebook, develop course materials, employ effective instructional methods, and inform teachers in this regard.